Nilai Dari Profesi Ibu Rumah Tangga dalam J-Dorama: Nigeru Wa Haji Da Ga Yaku Ni Tatsu - Hidayatullah, Arsy Dzikri Izza Arzaqi; Srimulyani, Nunuk Endah (KIRYOKU, 2021)
Unpaid work and gender equality are interrelated in the realm of gender studies. One of them is a gender sociology study regarding the position of housewives in the private sphere to do domestic work and carework as mushou roudou because they are considered to have no commodity value. The position of housewives becomes invisible because they do not get more attention from the community. Therefore, the purpose of this study is to describe the professional value of housewives through the analysis of Drama Nigeru wa Haji da ga Yaku ni Tatsu. The theory used in the analysis is the theory of mushou roudou vs. yuushou roudou to see the actual commodity value of domestic work and carework done by housewives when it is converted into yuusho roudou. The results of the analysis show that the domestic work and carework that housewives do actually have a commodity value like yuushou roudou with the discovery of several methods of calculating the compensation that housewives are entitled to receive.